Wanita Inspiratif dalam Kajian Tafsir Al-Qur’an - Roikhatul Jannah, Siti Nur; Erwanto, Dian (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
Women are half of society and the male half, as the Prophet Muhammad has said. A society will be good if both men and women are good. In the current era, women really need inspiration from female role models. This study describes the inspirational female figures in the Qur'an who serve as role models for women. Using the interpretation perspective, this research takes 7 inspirational women whose stories have been immortalized in the Al-Qur'an. Seven female figures who are only mentioned in the Qur'an must be set as role models, including Imron's wife, Maryam bint Imran, Ibrahim's wife, Queen Balqis, Musa's mother, two Madyan women and Asiyah bint Muzahim. Based on the stories of these inspiring women, an inspiration or example is obtained, including: from Hanna's story we can learn that humans must be able to accept God's destiny sincerely, even though this destiny does not match expectations. Likewise with Maryam's story, from her, we can learn that women must be good at maintaining honor.